The Use of ‘Snakes And Ladders’ Game As A Medium to Improve the Students’ Mastery of Past Form of Irregular Verbs - Ratnawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2023)
This study is about the use of „Snakes and Ladders‟ game toward the students‟ mastery of past form of irregular verbs. The study is aimed to (1) find out whether teaching the past form of irregular verbs by using „Snakes and Ladders‟ game is effective to improve the students‟ achievement in learning the verbs, and (2) find out the students‟ attitude and feeling toward the use of „Snakes and Ladders‟ game. The subjects of this study were the students of IX D of SMP N 5 Tambusai Utara. The selection of the class was based on the suggestion of the English teacher. The researcher used an action research design. There were two cycles in this study. Every cycle consisted of planning, acting, observing and reflecting. Before conducting the cyclical activities, the researcher gave the students an Initial Pre-test. After that, she gave the treatments to the students. In Cycle 1, she used group work without classical problem solving and showing the spelling of the verbs. However, the result was not satisfying enough. In Cycle 2, she used classical problem solving and also showing the spelling of the verbs. In this cycle, the result was very satisfying. After the cycle 2 was finished, she gave a Final Post-test and also questionnaire to the students. Based on the data analysis, there was a significant improvement of the students‟achievement after the use of „Snakes and Ladders‟ game was given. This improvement was proved by the comparison between the result of Initial Pre-test (68.14) and that of Final Post-test (88.80). After being showed the spelling of the verbs, their understanding toward the verbs was better. The classical problem solving that the researcher used in Cycle 2 successfully helped students learn the verbs from their friends‟ incorrect answers. The results of the observation checklists showed that the students‟ attitude in Cycle 2 was better than that in Cycle 1. Based on the result of questionnaire, the students also supported the use of „Snakes and Ladders‟ game in the teaching of grammar, especially the past form of irregular verbs. It was proved by their positive responses in relation to the use of that medium. Based on the results of the analysis above, it can be concluded that the use of „Snakes and Ladders‟ game successfully improves the students‟ mastery of past form of irregular verbs in the teaching of grammar.